BIBLIOMETRIC METHODS FOR SCIENTIFIC RESEARCH - Rzhevtseva, Nataliia L. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The method of assessments of published works (quantitative, statistic and index citation methods used in scientometrics and bibliometrics for scientific research) are considered.